(untitled) (Texas Journal of Medical Science, 2023)
In conclusion, we can say that during the transition of the muscular-elastic arteries to the muscular arteries on the side of the adventitia, an additional muscle layer is formed, which surrounds the vessel wall in the form of a spiral. As a result, the size of the middle layer of the artery increases. This leads to a change in the Kernogh index